Analisis Profitabilitas Dan Efisiensi Teknis Usahatani Padi Sawah Varietas Sigupai Abdya Di Kabupaten Aceh Barat Daya - Firdaus Firdaus; Sri Fitri; Fauzi Fauzi (Jurnal Agrisep, 2016)
The level of efficiency will be greatly influenced by the managerial capability of farmers in technology applications pre-harvest and post-harvest, as well as the ability of farmers to accumulate and process information relevant to the business of cultivation, so that decision-making can be done properly. The profitability of paddy farming sigupai local varieties becomes very important to be known as a material consideration in decisions about the use of technology in order to increase production and increase farmers' profits. Ability varieties of paddy farming sigupai generate profits (profit) is Rp. 2,564,793 per hectare per cropping season. Return on Invested Capital value of 0.49, suggesting that the ability of rice farming in paddy varieties sigupai restore their capital is still low. When viewed from the point of profitability ratio that is directly related (directly related) or in other words the value of Operating Ratio is at 0.67 and the value of Gross Ratio was 0.87. This indicates that the varieties of paddy rice farming sigupai able to generate sufficient benefits for farmers as organizers.The results of multiple regression analysis, using SPSS ( Statistical Package for the Social Sciences), the result that the labor factor ,seeds and fertilizer SP36, significant effect on the level of = 0.05, while other factors was not significant(non-significant). Judging from the relationship between the dependent variable with the independent variable was obtained for R = 99.70, while the variation that occurs is equal to R2 = 99.30, and a value of 0.70 is determined outside the model set. From the analysis of the level of efficiency is gained ln = 0.472, with otherwords that factors of production are not efficient, means of production factors still need to be added, except for a relatively efficient seed factor ( 0.891 ) .